Corneal oedema post phacoemulsification surgery: a comparison between type 2 diabetic and non-diabetic patients - Qasim, Bisma; Nisar Ahmed Siyal; Saleem, Maria; Muhammad Adnan; Muhammad Nizamuddin (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the association of post-phacoemulsification surgery corneal oedema between type 2 diabetic and non-diabetic patients in a tertiary care setting. Method: The prospective cohort study was conducted from November 2024 to February 2025 at the Ophthalmology Department of Dow University Hospital, Karachi, and comprised patients of either gender undergoing phacoemulsification. The patients were stratified into study group A comprising type 2 diabetics and the non-diabetic control group B. Standardised phacoemulsification was performed and postoperative evaluations were conducted on days 1, 7 and 30. Corneal oedema incidence and severity were compared between the groups. Data was analysed using SPSS 26. Results: Of the 100 patients, 50(50%) were in group A; 28(56%) females and 22(44%) males with mean age 60.3 ± 5.98 years. There were 50(50%) patients in group B; 34(68%) females and 16(32%) males with mean age 60.1± 6.17 years (p>0.05). On postoperative day 1, corneal oedema was observed in 36(72%) patients in group A compared to 18(36%) in group B (p<0.001). Group A patients had a significantly higher incidence of severe corneal oedema on day 1 (p=0.003) and day 7 (p=0.009), with a 7.6-fold increased likelihood compared to non-diabetics (odds ratio: 7.6; 95% confidence interval: 1.8-30; p<0.01). In group A, oedema was more frequent in uncontrolled diabetics having glycated haemoglobin >7% (p<0.05). Uncorrected visual acuity (6/6-6/12) on postoperative day 1 was achieved in 16(32%) group A patients compared to 26(52%) in group B. By day 30, 62(62%) of all the patients achieved uncorrected visual acuity of 6/6. Conclusion: The likelihood of post-phacoemulsification corneal oedema was greatly increased by type II diabetes, particularly when it was poorly controlled, and it also slowed vision recovery. Key Words: Diabetes mellitus, Type II phacoemulsification, Corneal oedema, Glycated haemoglobin, Prospective studies, Treatment outcome.